Deregulated ERK1/2 MAP kinase signaling promotes aneuploidy by a Fbxw7β-Aurora A pathway. Issue 12 (17th June 2016) - Duhamel, Stéphanie; Girondel, Charlotte; Dorn, Jonas F.; Tanguay, Pierre-Luc; Voisin, Laure; Smits, Ron; Maddox, Paul S.; Meloche, Sylvain
ABSTRACT: Aneuploidy is a common feature of human solid tumors and is often associated with poor prognosis. There is growing evidence that oncogenic signaling pathways, which are universally dysregulated in cancer, contribute to the promotion of aneuploidy. However, the mechanisms connecting signaling pathways to the execution of mitosis and cytokinesis are not well understood. Here, we show that hyperactivation of the ERK1/2 MAP kinase pathway in epithelial cells impairs cytokinesis, leading to polyploidization and aneuploidy. Mechanistically, deregulated ERK1/2 signaling specifically downregulates expression of the F-box protein Fbxw7β, a substrate-binding subunit of the SCF Fbxw7 ubiquitin ligase, resulting in the accumulation of the mitotic kinase Aurora A. Reduction of Aurora A levels by RNA interference or pharmacological inhibition of MEK1/2 reverts the defect in cytokinesis and decreases the frequency of abnormal cell divisions induced by oncogenic H-Ras V12 . Reciprocally, overexpression of Aurora A or silencing of Fbxw7β phenocopies the effect of H-Ras V12 on cell division. In vivo, conditional activation of MEK2 in the mouse intestine lowers Fbxw7β expression, resulting in the accumulation of cells with enlarged nuclei. We propose that the ERK1/2/ Fbxw7β/Aurora A axis identified in this study contributes to genomic instability and tumor progression.